Trend of stillbirth and associated factors among women who gave birth at a specialized hospital in northern Ethiopia: A 10-year record review - Meles, Gebrekiros Gebremichael; Berhe, Yibrah; Abraha, Zewde; Beyene, Wegen; Moges, Yonas; Tsadik, Mache; Haile, Tsadkan Gebremeskel; Berhe, Gebreslassie Gebremariam; Amare, Yemane; Yemane, Awol; et al. (Ethiopian Journal of Reproductive Health, 2025)
Background: Stillbirths are the most significant indicators of maternal and infant health care. Even with the numerous attempts by international organizations to lower the number of stillbirths, low- and middle-income countries, especially Ethiopia, face formidable obstacles in tackling this problem. Therefore, this study aimed to estimate the stillbirth rate and trends among mothers who delivered at Ayder Comprehensive Specialized Hospital, Northern Ethiopia. Methods: A retrospective analysis of birth registries was conducted at Ayder Comprehensive Specialized Hospital, which is located in Tigray, Northern Ethiopia. We prepared a checklist to extract the available information from the birth records from July 2011 to August 2021. We collected the data via an open data kit tool. A binary logistic regression model was used to identify the factors associated with stillbirth, and an odds ratio with a 95% confidence interval was used to assess the strength of the association. Results: Over the course of the 10-year study period, the researchers discovered that there were 51.3 stillbirths for every 1000 live births (95% CI: 48.7-54.0). A stillbirth from a mother aged 36-50 years (AOR=1.97, 95% CI: 1.56-2.48), an unstable maternal health status (AOR=100.1, 95% CI: 71.38-140.38), a male newborn (AOR=1.25, 95% CI: 1.09-1.44), low and very low birth weights (AOR=29.77, 95% CI: 24.46-36.25), and a singleton birth (AOR=0.43, 95% CI: 0.32-0.58) were the factors that were independently associated with stillbirth. Conclusion: The stillbirth rate was alarmingly higher in this study, indicating that immediate attention is needed. Interventions that address low birth weight, advanced maternal age, and maternal health status should be prioritized in the fight to lower the stillbirth rate.